PENGARUH NILAI PERUSAHAAN, LEVERAGE DAN FINANCIAL DISTRESS TERHADAP KEPUTUSAN HEDGING STUDI KASUS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Ahmad Pati Hulmubin; Furqonti Ranidiah; Yudi Partama Putra; Diah Khairiyah (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
financial distress on hedging decisions in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The method used is a quantitative approach with logistic regression analysis techniques. The sample consisted of 45 companies selected using a purposive sampling method. The independent variables studied include firm value (Market to Book Value), leverage (Debt to Equity Ratio), and financial distress (Altman Z-Score), while the dependent variable is the hedging decision measured using a dummy. The results show that firm value has a positive and significant effect on hedging decisions, while leverage and financial distress have a negative and significant effect. Simultaneously, these three variables have a significant influence on hedging decisions. However, the ability of these three variables to explain hedging decisions is only 7.8%, the rest is influenced by other factors outside the research model. Keywords: Firm Value, Leverage, Financial Distress, Hedging Decisions, Logistic Regression